2008
DOI: 10.1097/pas.0b013e31816098f0
|View full text |Cite
|
Sign up to set email alerts
|

Vascular “Pseudo Invasion” in Laparoscopic Hysterectomy Specimens: A Diagnostic Pitfall

Abstract: Total laparoscopic hysterectomy has been shown to be an equally effective and safe technique when compared with conventional abdominal surgery for endometrial carcinoma. The procedure, as performed at our institution, involves the use of a uterine balloon manipulator (RUMI manipulator and Koh Colpotomizer system) for optimal surgical control. The fallopian tubes are cauterized to prevent transtubal spread of the tumor. The balloon manipulator thus creates a positive closed pressure system within the uterine ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 18 publications
0
59
1
1
Order By: Relevance
“…In contrast to the two previously published studies, which addressed vascular space involvement by endometrial carcinoma in total laparoscopic hysterectomies, 7,8 this study did not find a significant difference in the rate of vascular space involvement between total laparoscopic hysterectomy and total abdominal hysterectomy. Nevertheless, there was a trend towards a higher frequency of vascular space involvement in the total laparoscopic hysterectomy group and the lack of a strong correlation can be related to a number of issues.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the two previously published studies, which addressed vascular space involvement by endometrial carcinoma in total laparoscopic hysterectomies, 7,8 this study did not find a significant difference in the rate of vascular space involvement between total laparoscopic hysterectomy and total abdominal hysterectomy. Nevertheless, there was a trend towards a higher frequency of vascular space involvement in the total laparoscopic hysterectomy group and the lack of a strong correlation can be related to a number of issues.…”
Section: Discussioncontrasting
confidence: 99%
“…Thirty-seven laparoscopic hysterectomies for benign (30) and neoplastic (7) conditions, including six grade 1 endometrioid cancers and one atypical complex hyperplasia, were originally examined. 7 The authors found tumor in blood vessels in 71% of the malignant total laparoscopic hysterectomies and benign glands and stroma in vascular spaces of 13% of benign cases. They concluded that total laparoscopic hysterectomy is associated with high rates of vascular pseudoinvasion, which is presumably caused by the increased intrauterine pressure created by the intrauterine manipulator.…”
mentioning
confidence: 99%
“…In both cervical and endometrial malignancies, clinico-pathological parameters such as infiltration depth and lymphovascular space invasion (LVSI) may be influenced when a manipulator is used [27][28][29][30][31]. However, it is hypothesised that other factors such as artefacts and tissue handling contributed to these findings.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this phenomenon can be described as vacuum effect in which the lymphovascular spaces in the endometrium collapse owing to positive pressure in the uterine cavity; this makes the myometrial vasculature accessible to dislodged endometrial glands and stroma. 88 Others propose that LVPI is a grossing artifact, arguing that displacement of endometrial glands and stroma is a result of manipulation of the specimen in the gross room and is more likely to occur in exophytic tumors. 87,89 However, it should also be noted that there can be significant interobserver variability in assessing lymphovascular space invasion.…”
Section: Lymphovascular ''Pseudoinvasion''mentioning
confidence: 99%